Prolonged exposure to resistin inhibits glucose uptake in rat skeletal muscles - Fan Hong-qi; Gu Nan; Liu Feng; Fei Li; Pan Xiao-qin; Guo Mei; Chen Rong-hua; Guo Xi-rong (Acta Pharmacologica Sinica, 2016)
Aim: To assess the effects and mechanisms of the action of resistin on basal and insulin-stimulated glucose uptake in rat skeletal muscle cells. Methods: Rat myo-blasts (L6) were cultured and differentiated into myotubes followed by stimulation with single commercial resistin (130 ng/mL, 0-24 h) or cultured supernatant from 293-T cells transfected with resistin-expressing vectors (130 ng/mL, 0-24 h). Liquid scintillation counting was used to quantitate [3H] 2-deoxyglucose uptake. The translocation of insulin-sensitive glucose transporters GLUT4 and GLUT1, synaptosomal-associated protein 23 (SNAP23) and GLUT protein content, as well as the tyrosine phosphorylation status and protein content of insulin receptor substrate (IRS) -1, were assessed by Western blotting. Results: Treatment of L6 myotubes with single resistin or cultured supernatant containing recombinant resistin reduced basal and insulin-stimulated 2-deoxyglucose uptake and impaired insulin-stimulated GLUT4 translocation. While SNAP23 protein content was decreased, no effects were noted in GLUT4 or GLUT1 protein content. Resistin also diminished insulin-stimulated IRS-1 tyrosine phosphorylation levels without affecting its protein content. The effects of recombinant resistin from 293-T cells transfected with resistin-expressing vectors were greater than that of single resistin treatment. Conclusion: Resistin regulated IRS-1 function and decreased GLUT4 translocation and glucose uptake in response to insulin. The downregulated expression of SNAP23 may have been partly attributed to the decrease of glucose uptake by resistin treatment. These observations highlight the potential role of resistin in the pathophysiology of type 2 diabetes related to obesity.